2014
DOI: 10.1007/s12630-014-0255-1
|View full text |Cite
|
Sign up to set email alerts
|

Bloc échoguidé du nerf saphène interne – à l’intérieur versus en position distale du canal des adducteurs: une étude randomisée de validation de principe

Abstract: In this randomized trial, we found no differences in nerve visibility, block success rate, or onset between the AC and Peri-SBDGA techniques of ultrasound-guided saphenous nerve blockade, although the former technique provided superior vascular landmark visibility. Neither technique produced a sufficiently high success rate to provide reliable surgical anesthesia per se.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 19 publications
0
17
2
1
Order By: Relevance
“…5 Block success at 30 minutes was not significantly different despite the more prominent vascular landmark in the adductor canal, and we found that neither technique offered a sufficiently high success rate to provide reliable surgical anesthesia.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…5 Block success at 30 minutes was not significantly different despite the more prominent vascular landmark in the adductor canal, and we found that neither technique offered a sufficiently high success rate to provide reliable surgical anesthesia.…”
mentioning
confidence: 62%
“…1,2 However, in part owing to its small caliber, the saphenous nerve is more difficult to reliably block than the sciatic nerve in the popliteal fossa (ie, with success rates reliably exceeding 95%). [3][4][5] As the terminal branch of the femoral nerve, the saphenous nerve provides sensory innervation to the anteromedial aspect of the lower leg, including the medial ankle joint capsule and distal tibia. 6 Extending proximally from the femoral triangle, it descends within the adductor canal, accompanying the femoral artery and nerve of vastus medialis beneath the sartorius muscle, and continues its course underneath the sartorius muscle until it penetrates the connective tissue between the tendons of the sartorius and gracilis muscles on the medial side of the knee.…”
mentioning
confidence: 99%
“…As for saphenous nerve blockade, recent studies have reported similar block characteristics whether low-volume injections (5-8 mL) were performed using the adductor canal versus the subsartorial approaches. 49,50 With regard to the sciatic popliteal approach, recent investigations consistently demonstrate improved block characteristics (onset time and/or performance time) when the local anesthetic is deposited within the subparaneural compartment (the paraneurium is a sheath deep to the epimysium that surrounds muscle tissue and superficial to the nerve's epineurium). 8,51,52 In summary, an abundance of new lower-extremity studies (mostly level Ib evidence) has served to reinforce our previous grade A recommendation that US improves block characteristics (onset time, performance time, and rate of complete sensory blockade) as compared with PNS techniques.…”
Section: Lower-extremity Blocksmentioning
confidence: 98%
“…In addition to housing the femoral artery and vein, the canal also contains the nerve to the vastus medialis muscle, the saphenous nerve, and the posterior division of the obturator nerve. 6 As such, effective sensory blockade of the knee joint can be achieved while theoretically sparing blockade of motor fibres supplying the quadriceps muscles. This results in shortened time to mobilization compared with conventional FNB.…”
mentioning
confidence: 99%
“…Outre le fait qu'il loge l'artère et la veine fémorale, ce canal contient également le nerf du muscle vaste interne, le nerf saphène, et la portion postérieure du nerf obturateur. 6 Dès lors, en théorie du moins, un bloc sensitif efficace de l'articulation du genou peut être réalisé tout en épargnant le bloc des fibres motrices qui alimentent le quadriceps. Ainsi, le délai jusqu'à la mobilisation est plus court par rapport à un BNF conventionnel.…”
unclassified